1996
DOI: 10.1177/004051759606600609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microfibril Orientation in Cotton Fibers by Fluorescence Polarization

Abstract: Microfibril orientation in a cotton fiber surface is measured by the fluorescence polarization method using microphotometry. To serve as a cotton model, drawn nylon fibers are dyed with a high concentration of fluorescent probe and subjected to a twist tester to obtain certain twisting angles, which are then quantitatively determined from the angular distribution of the polarized fluorescence intensity. For naturally dried cotton fibers, this fluorescence polarization analysis shows the twisting angle to be 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Thus, it can be said that the cellulose microfibrils in locations 7 and 8 are relatively parallel to the laser incidence plane. Overall, the data presented in Figure are congruent with the fact that the microfibril angle with respect to the fiber axis varies from locations to locations along the cotton fiber. , …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, it can be said that the cellulose microfibrils in locations 7 and 8 are relatively parallel to the laser incidence plane. Overall, the data presented in Figure are congruent with the fact that the microfibril angle with respect to the fiber axis varies from locations to locations along the cotton fiber. , …”
Section: Resultssupporting
confidence: 78%
“…Overall, the data presented in Figure 4 are congruent with the fact that the microfibril angle with respect to the fiber axis varies from locations to locations along the cotton fiber. 59,60 Because the SFG coherence length is longer in the forward scattering direction than in the backward scattering direction, 61,62 the SFG intensity is generally higher in the transmission-mode detection than in the reflection-mode detection. Figure 5 compares the SFG hyperspectral images and full spectra of cotton fibers collected in the reflection-and transmission-mode detections.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…First, the effect of the cultivating method, namely comparing cotton fiber grown using agricultural chemicals with organically grown cotton fiber, and comparing cotton yarns made of non-organic or organic cotton fibers. The sec-ond point is the effect 1 of the area of cultivation, namely whether the fiber was cultivated in the northern or southern hemisphere. This point of view is based on research by Onogi [1].…”
Section: Masako Niwamentioning
confidence: 99%
“…The sec-ond point is the effect 1 of the area of cultivation, namely whether the fiber was cultivated in the northern or southern hemisphere. This point of view is based on research by Onogi [1]. It has been reported that the rules of surface orientation differ for cotton fibril cultivated in the northern and southern hemispheres, regardless of the growing regions and the kinds of cotton.…”
Section: Masako Niwamentioning
confidence: 99%
“…A slight change in orientations of ribbonlike bers is likely to change the scattered-light pro les signi cantly. 6 Given this, it is crucialto know the orientation of bers in order to make unambiguousand reasonable comparisons against the numerical predictions. Finding a location where the laser light would be incident on a ber surface perpendicularly is dif cult.…”
Section: Cotton-fiber Samplesmentioning
confidence: 99%